128k views
4 votes
Prove that : 1/1-secA + 1/1+secA = -2cot^2A​

User Mtekeli
by
5.1k points

1 Answer

5 votes

Answer:

Explanation:

LHS = 1/1-secA + 1/1+secA


= (1*(1+Sec A))/((1-Sec A)(1+Sec A))+(1*(1-Sec A))/((1+Sec A)*(1-Sec A))\\\\=((1+Sec A))/(1-Sec^(2) A)+((1-Sec A))/(1-Sec^(2) A)\\\\=(1+Sec A+1-Sec A)/((1-Sec^(2) A))\\\\= (2)/((1-Sec^(2) A))\\\\=(2)/(-(Sec^(2) A - 1))\\\\= (-2)/(Tan^(2) A)\\\\= -2Cot^(2) A

Prove that : 1/1-secA + 1/1+secA = -2cot^2A​-example-1
User Pellay
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.